7n=n+6(8n-7)

Simple and best practice solution for 7n=n+6(8n-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7n=n+6(8n-7) equation:


Simplifying
7n = n + 6(8n + -7)

Reorder the terms:
7n = n + 6(-7 + 8n)
7n = n + (-7 * 6 + 8n * 6)
7n = n + (-42 + 48n)

Reorder the terms:
7n = -42 + n + 48n

Combine like terms: n + 48n = 49n
7n = -42 + 49n

Solving
7n = -42 + 49n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-49n' to each side of the equation.
7n + -49n = -42 + 49n + -49n

Combine like terms: 7n + -49n = -42n
-42n = -42 + 49n + -49n

Combine like terms: 49n + -49n = 0
-42n = -42 + 0
-42n = -42

Divide each side by '-42'.
n = 1

Simplifying
n = 1

See similar equations:

| 4t-1=3t+7 | | x^2-16=2x^2-14x+21 | | 4x+5=10x-23 | | -.75n+7=25 | | 3-.2x=.3x-7 | | 5x-6=1-2x | | (a+3b)x+(a+3b)y= | | 8b+3b-6=38 | | 0.6666666666x-4=10 | | -2x+8=-6+5 | | -2(-10)-y=16 | | x+y=630 | | 6s-2=5s+10 | | 12-.6x=-27 | | (16x+5y)dx+(3x+y)dy=0 | | x*x=-36 | | 2x^3-8x^2-14x= | | 10x=4.09 | | n^3-n-3360=0 | | e^1-7x=9 | | (6-v)(3v-4)=0 | | x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 |

Equations solver categories